Ghanshyam Das Birla - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2023)
Ghanshyamdas Birla was a great son of India. There is hardly an aspect of national life which he did not enrich by his business acumen, patriotic fervor and philanthropy born of his deep personal attachment to Mahatma Gandhi. He gave substantial financial aid to the Mahatma's constructive programmes. Ghanshyamdas Birla was also closely associated with other important leaders of his time, such as Lokamanya Tilak, Motilal Nehru, Madan Mohan Malaviya, Sardar Vallabhbhai Patel and Jawaharlal Nehru.
Keywords: Visionaries; Biography- Ghanshyam Das Birla(1894-1983)